Perspective about Definition of Individual with Special Needs from Several Scientific Fields: A Short Note - Ediyanto Ediyanto; Thalsa Syahda Aqilah; Mohammad Efendi (Department of Special Education, 2022)
This short article aims to provide an understanding that there are several points of view about individuals with special needs. Some of these points of view may differ in defining individuals with special needs. So that the optimization of a felicitous life for individuals with special needs may not match what they actually need.